Campus universitário como laboratório vivo para sustentabilidade: proposição de critérios analíticos - Pantaleão, Cristiane Criscibene (2017)
Higher Education Institutions (HEI) can function as small urban centers, as well as living laboratories and reference in the dissemination of sustainability concepts, fostering this culture in the global community, and are not limiting its perimeter. The objective of this work is to propose an adaptive analytical framework with criteria that lead a university campus to be characterized as a Living Laboratory for Sustainability. In this study, an applied research was carried out with a qualitative approach and a research strategy and an exploratory category with a case study. Initially, a systematic analysis of the literature and bibliometric revision were carried out, with the objective of finding scientific papers related to the topic, besides serving as a guide for the direction, revisions and later validation of the choices. The object of the case study for a Brazilian HEI engaged in the pursuit of sustainable development, which has many sustainability actions in operations and which had its campus considered the most sustainable in Latin America in 2015 and 2016. These actions show signs that the IES may come Living Laboratory for Sustainability. In addition to the empirical analysis, a documentary analysis of an international HEI was developed, Which considers its campus as a Living Lab for Sustainability. The evidences found present examples of HEI with well established environmental policies, several actions in operation, projects and campaigns in progress. According to the results, an end to a Living Lab for Sustainability is characterized, it is necessary that live and experienced practices, communication and community building of the academic community and interaction with an external community. In addition to contributing to the academic community, this scientific study can guide how HEI and other organizations that wish to follow the path of sustainable development, becoming a reference in environmental management in a society and in the formation of people aware of their planetless role.